Development of a multi-functional chamber for resonant X-ray scattering experiments in the tender X-ray regime at the PAL-XFEL - Soon Hee Park; Seonghan Kim; Jaeku Park; Seokhwan Yun; Jaehong Jeong; Je-Geun Park; Kyung Sook Kim; Tae-Kyu Choi; Intae Eom; Dogeun Jang; Minseok Kim; Jae Hyuk Lee; et al. (Journal of Synchrotron Radiation)
The hard X-ray undulator line at Pohang Accelerator Laboratory X-ray Free Electron Laser (PAL-XFEL) provides a wide range of photon energies encompassing both the tender (2–5 keV) and hard (5–15 keV) X-ray regimes. Its Femtosecond X-ray Scattering (FXS) endstation is dedicated to research in condensed matter physics and materials science, and supports various time-resolved X-ray experiments, such as diffraction, spectroscopy and resonant X-ray scattering. We report the development of a multi-functional chamber at the FXS endstation to support the experiments in the tender X-ray regime where significant air scattering and absorption pose challenges. This chamber enables optical-pump/X-ray-probe experiments in a vacuum environment, with its functionality demonstrated through time-resolved resonant elastic X-ray scattering experiments on a ruthenate Li2RuO3 near the Ru L3 (∼2.84 keV) absorption edge. Designed to readily accommodate modular instruments, the chamber offers flexibility to provide diverse experiment conditions requested by users at the FXS endstation.